(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Background: Maternal morbidity related to infection after caesarean section has been reported to be higher than that of vaginal delivery. The prevention of infection in patients undergoing caesarean section is a major challenge, particularly in hospitals, where there is frequent chance of cross infection due to overcrowding. Objective: The present study was undertaken to see the efficacy of single dose cetriaxone as a prophylaxis in elective caesarean section to prevent postoperative infection. Methods: This cross sectional study was conducted on 100 patients who underwent elective caesarean section where single dose of Ceftriaxone was used as prophylaxis in the Department of Obstetrics & Gynaecology, Bangabandhu Sheikh Mujib Medical University Hospital, between January to June 2010. The outcomes measures were postoperative febrile morbidity, wound infe-ction and other infections (urinary tract infection, chest infection). Data were analysed using statistical package for social sciences (SPSS) version 11.5. Results: Over one-third (38%) patients age group was between 18 -25 years, 56% in between 25 -35 years and 6% were over 35 years old. Nearly half(46%) was anemic (haemoglobin< 11 g/dl) and 16% was obese (BMI?28 kg/m2). All the patients were operated by obstetricians of same level. Three per cent patients developed wound infection, 5% developed other infections like UTI and chest infection and 7% had febrile illness. Among the several factors suspected to be associated with post operative complications, preoperative anaemia, long duration of operation (>60 minutes) and prolonged hospital stay (>1 week) were found to be significantly assocated with postoperative complications. Conclusion: The present study suggests that single dose prophylactic antibiotic ceftriaxone given 1 hour before operation in patients with cesarean section deliveries reduces the chance of postoperative infection to a bare minimum.